Evaluation of drug loading capacity and release characteristics of PEDOT/naproxen system: Effect of doping ions. (1st November 2018) - Krukiewicz, Katarzyna; Kruk, Aleksandra; Turczyn, Roman
Abstract: Conducting polymers are versatile and robust materials that have recently become attractive as controlled drug delivery systems. Possessing ion exchangeable properties, they can serve as carriers for numerous biologically active species, showing particular applicability in neural tissue engineering and regional chemotherapy. In the pursuit of the design of the most effective controlled drug delivery system, we aimed to compare the performance of the conducting polymer-based matrix as a function of doping anion, using chloride, perchlorate and dodecyl sulfate, respectively, as the primary dopants. Due to their different ion radius and mobility, selected ions were found to provide substantial changes into polymer characteristics, having strong effects into the uptake and release of a model drug, naproxen sodium salt. PEDOT/ClO4 matrix, particularly, was found to possess superior properties providing highest mass of the formed polymer (103.45 ± 10.09 μg cm −2 ), charge storage capacity (44.9 mC cm −2 ) and ion exchange capacity (0.122 ± 0.003 μmol cm −2 ), leading also to the highest amounts of loaded (0.024 ± 0.002 μmol cm −2 ) and released (from 0.71 ± 0.10 μg cm −2 to 1.61 ± 0.59 μg cm −2 ) drug. Highlights: Performance of PEDOT as a carrier for naproxen is compared for selected primary dopants. EQCM is employed to monitor the doping processes in situ . Ion exchange capacity is found to be dopant-dependent. Mobility of primary dopant is shown to influence drug availability. Drug loading capacity is confirmed to be intrinsic property of polymer matrix.